KETERSEDIAAN SUMBER AIR BERSIH UNTUK PEMENUHAN KEBUTUHAN RUMAH TANGGA DI DESA FATUKETI KECAMATAN KAKULUK MESAK KABUPATEN BELU - Tahu, Eletria S; Hasan, Muhammad Husain; Manek, Agustinus Hale (Jurnal Geografi, 2023)
This study aims to 1) determine the availability of clean water sources used by residents to meet household needs. 2) find out what efforts are being made by the community to overcome the shortage of clean water in Fatuketi Village, Kakuluk Mesak District, Belu Regency. This type of research uses a qualitative approach with data collection methods: observation, interviews and documentation. The subjects of this research were the people of Fatuketi village from four hamlets and the object of this research was the residents' dug wells in studying the availability of clean water sources to fulfill household needs. The results of this study found that the availability of clean water in Fatuketi village was lacking, namely judging from the distribution of wells, there were nine dug wells taken from four hamlets because the least available water source was in four hamlets, including: Fatubesi Hamlet, Sureu Hamlet, Amoro Hamlet and also Dusun Fukalaran. From the availability of clean water sources in Fatuketi Village, some use tank water 51% and well water 49%. In tackling the shortage of clean water in Fatuketi village, Kalukuk Mesak sub-district, they are trying to buy a tank. There are also those who collect well water by accessing clean water using motorbikes or carts for a distance of 70-100 meters. The community seeks access at such a distance in order to meet their daily needs, namely: bathing, washing, cooking, and watering the plants.